Global entrepreneurship, institutions and incentives the Mason years - Acs, Zoltán J. 1947- (Edward Elgar Pub. Ltd, 2015)
This book presents some of Zoltán J. Ács' most important contributions since the turn of the new millennium, with a particular intellectual focus on knowledge spillover entrepreneurship. It studies the evolution of global entrepreneurship and pays attention to the role of institutions and the incentives they create for economic agents who become either productive or unproductive entrepreneurs. For productive entrepreneurs, those that create wealth for themselves and for society, the author offers a knowledge spillover theory of entrepreneurship as a new way to help understand the entrepreneurial ecosystem. For those that create wealth only for themselves the author develops a theory of destructive entrepreneurship that undermines the entrepreneurial ecosystem. The book also presents an explanation of the role of philanthropy in reconstituting wealth to complete the circuits of capital in the theory of capitalist development. Finally, the author examines several public policy issues including immigration and technology transfer. This volume will be required reading for students and scholars of entrepreneurship, economics and public policy
Includes index
Keywords: Entrepreneurship; Entrepreneurship / Political aspects; Globalization; Entrepreneurship / Social aspects; Electronic books